New information on the biology and control of Cinara tujafilina (Del Guercio) (Aphidoidea Lachnidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence of Cinara tujafilina in Europe on the roots of Thuja orientalis cultivated in pots before planting is reported. After three years of observation, the biological cycle of the aphid is described as well as indications on techniques for controlling it.